Proposed Framework To Explore The Role Of Consumer Protection And Ecosystem Orchestration In The Banking Industry: Supporting SDG 9 - Anto Prabowo; Wimboh Santoso; Djoko Suhardjanto; Irwan Trinugroho (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: The banking industry is experiencing significant transformation driven by increasing demands for consumer protection and digital ecosystem development. This study aims to propose a conceptual framework for examining the role of consumer protection and ecosystem orchestration in improving financial and digital performance within the banking industry. The study contributes to Sustainable Development Goal (SDG) 9 by highlighting the importance of innovation and digital infrastructure development in strengthening the competitiveness of financial institutions. Method: A conceptual research approach based on the Structure-Conduct-Performance (SCP) paradigm. The proposed framework integrates firm size as a structural variable, consumer protection and ecosystem orchestration as conduct variables, and financial performance and digital performance as outcome variables. The conceptual model is developed through theoretical exploration of previous studies related to banking transformation, consumer protection, digital ecosystems, and organizational capabilities. Results: The proposed framework suggests that firm size may influence consumer protection and ecosystem orchestration capabilities, while both consumer protection and ecosystem orchestration are expected to contribute to financial performance and digital performance. The framework provides a comprehensive perspective on how banks can balance digital innovation with consumer trust and protection. Novelty: The study offers a novel integrated framework by combining consumer protection and digital ecosystem orchestration within the SCP paradigm. The proposed model provides a foundation for future empirical research examining how banking institutions can achieve sustainable digital transformation aligned with SDG 9.